2017
DOI: 10.1016/j.jallcom.2016.09.218
|View full text |Cite
|
Sign up to set email alerts
|

Optical and X-ray induced luminescence from Eu3+ doped La2Zr2O7 nanoparticles

Abstract: Nanocrystalline complex oxide scintillators have emerged for use in X-ray and gamma-ray detection in recent years. Here the doping concentration dependence of europium-doped lanthanum zirconate (La2Zr2O7:xmol%Eu 3+ , x = 1 to 35) nanoparticles (NPs) were investigated by using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, scanning electron microscopy (SEM), and optically and X-ray excited luminescence. Spectroscopic methods revealed a gradual increase in disorder from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 71 publications
2
29
0
2
Order By: Relevance
“…Increasing the CoWO 4 content in BiOBr reduces the fluorescence lifetime of the composites. Similar effects were reported by Pokhrel et al . The decay curves of the BiOBr–CoWO 4 nanocomposites revealed that energy transfer and decay processes were dependent on the amount of CoWO 4 nanoparticles in the composite.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the CoWO 4 content in BiOBr reduces the fluorescence lifetime of the composites. Similar effects were reported by Pokhrel et al . The decay curves of the BiOBr–CoWO 4 nanocomposites revealed that energy transfer and decay processes were dependent on the amount of CoWO 4 nanoparticles in the composite.…”
Section: Resultsmentioning
confidence: 99%
“…These properties make them suitable for scientific and technological applications such as thermal barrier coatings, magnetic materials, electrocatalysis, sensors, optical materials, solid‐oxide fuel cells, high level nuclear waste hosts, etc. Moreover, recently relevant nanostructured pyrochlore materials have gained significant attention compared with their bulk counterparts in the areas of photoluminescence, scintillation, and magnetism …”
Section: Introductionmentioning
confidence: 99%
“…They are thermally stable, can accommodate dopant ions at both A and B sites, and have high radiation stability, etc. Hence, they are predominately used as hosts in the production of doped inorganic phosphors . Moreover, lanthanum‐based pyrochlores are known to exhibit excellent thermal stability, high thermal shock resistance, and fracture toughness compared to ytrria‐stabilized zirconia (YSZ) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations